2020
DOI: 10.3390/nano10020258
|View full text |Cite
|
Sign up to set email alerts
|

Perfect Absorption Efficiency Circular Nanodisk Array Integrated with a Reactive Impedance Surface with High Field Enhancement

Abstract: Infrared (IR) absorbers based on a metal–insulator–metal (MIM) have been widely investigated due to their high absorption performance and simple structure. However, MIM absorbers based on ultrathin spacers suffer from low field enhancement. In this study, we propose a new MIM absorber structure to overcome this drawback. The proposed absorber utilizes a reactive impedance surface (RIS) to boost field enhancement without an ultrathin spacer and maintains near-perfect absorption by impedance matching with the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Where 'ng,2D' is the carrier concentration in the two dimensional graphene material, 'vF' is the Fermi velocity (≈1×10 6 m/s), and 'kF' is the Fermi wave vector. Moreover, this is the simple motive of graphene material for optical characteristics, enormous carrier mobility and interband transitions [22,23].…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Where 'ng,2D' is the carrier concentration in the two dimensional graphene material, 'vF' is the Fermi velocity (≈1×10 6 m/s), and 'kF' is the Fermi wave vector. Moreover, this is the simple motive of graphene material for optical characteristics, enormous carrier mobility and interband transitions [22,23].…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Cesario et al have validated a structure for controlling the scattering of incident light by coupling the plasmonic nanoparticles with a metallic mirror separated using a dielectric cavity [48]. It has been demonstrated that, excitation and coupling of localized surface plasmon supported by the nanoparticle and propagating surface plasmon supported by the film result in a multiple resonance response [43,49,50]. Various groups have investigated the effect of enhancing the absorption by these cavity-coupled structures for realizing plasmonic perfect absorbers [38,43,44,[49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that, excitation and coupling of localized surface plasmon supported by the nanoparticle and propagating surface plasmon supported by the film result in a multiple resonance response [43,49,50]. Various groups have investigated the effect of enhancing the absorption by these cavity-coupled structures for realizing plasmonic perfect absorbers [38,43,44,[49][50][51][52]. Broadly two different approaches are employed for realizing perfect absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the RIS can improve antenna impedance matching by offsetting the capacitive near-field characteristic of the antenna through its inductive surface impedance characteristic [41]- [43]. Recently, the RIS was utilized in a MIM (metalinsulator-metal) absorber design in the near-IR range and the structure showed the increase of field enhancement along with nearly perfect absorption due to the impedance matching between the structure and the vacuum [44]. In our study, we applied both HIS and RIS to bowtie nanoantenna design to achieve the maximum field enhancement and perfect absorption at the same time.…”
Section: Introductionmentioning
confidence: 99%